2017
DOI: 10.1007/s00414-017-1662-y
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating human versus non-human bone by exploring the nutrient foramen: implications for forensic anthropology

Abstract: One of the roles of a forensic anthropologist is to assist medico-legal investigations in the identification of human skeletal remains. In some instances, only small fragments of bone may be present. In this study, a non-destructive novel technique is presented to distinguish between human and non-human long bones. This technique is based on the macroscopic and computed tomography (CT) analysis of nutrient foramina. The nutrient foramen of long bone diaphyses transmits the nutrient artery which provides much o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Similarly, our study also showed that all nutrient artery canals of the femur in the cortex on CTL radiographs course upward obliquely from posterodistal to anteroproximal direction. This fact supports the suggestion of Johnson et al 16 that nutrient artery canal could be used to discriminate between human and nonhuman bone.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, our study also showed that all nutrient artery canals of the femur in the cortex on CTL radiographs course upward obliquely from posterodistal to anteroproximal direction. This fact supports the suggestion of Johnson et al 16 that nutrient artery canal could be used to discriminate between human and nonhuman bone.…”
Section: Discussionsupporting
confidence: 91%
“…Nutrient arteries and their canals have been studied by observing the dry bones3413 or perfused bones,1415 radiological study,14 and multidetector computed tomography (MDCT) 1116. However, there have been few relevant data on differentiating nutrient artery canals from fracture lines on plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion criteria were (1) absence of evidence of pathological or curatorial damage; (2) being adults as evidenced by the closure of epiphyseal growth plates and (3) the new subset of measurements were performed when at least one well-defined nutrient foramen (NF) could be located on the diaphysis. The dominant nutrient foramina were initially identified in the unsexed sample by the elevated margins and distinct groove leading to the external orifice (Hughes, 1952) and by being capable of admitting at least the tip of a 24-gauge hypodermic needle, whereas those smaller were not analysed (Johnson et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Even fewer studies have focused on the comparison between human and non-human nutrient foramina, in the field of comparative anatomy or forensic anthropology. Johnson et al (2017) measured the location (based on the calculation of the foraminal index, not used in this study), direction, length, angle, circumference and area of the main nutrient canal in human, pig and sheep humeri and femora, in order to identify new parameters that could be used in the differentiation between human and non-human bones in forensic contexts. In this latter study, the circumference and cross-sectional area of the nutrient canal were not found to be useful for human/non-human differentiation, as there were no significant differences among the species considered.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this study, however, is that only 36 bones were analysed, and only two non-human species were considered. Furthermore, since Johnson et al's (2017) study focused only on humeri and femora, its results might not be applicable in cases where other long bones such as radii, ulnae or tibiae are found.…”
Section: Introductionmentioning
confidence: 99%